2019
DOI: 10.1002/clc.23269
|View full text |Cite
|
Sign up to set email alerts
|

Patients report more severe daily limitations than recognized by their physicians

Abstract: BackgroundPatient limitations guide selection of heart failure therapies, for which indications often specify New York Heart Association Class.ObjectivesTo determine the extent of patient‐reported limitations during daily activities and compare to New York Heart Association class assigned by providers during the same visit, and to left ventricular ejection fraction (LVEF) group.Methods and ResultsWhile waiting for their appointment, 948 patients on return visits to an ambulatory HF clinic completed a written q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Much of the burden related to HFpEF can typically be attributed to a high prevalence of co‐morbidities, such as diabetes, obesity, hypertension, anaemia, chronic kidney disease (CKD), atrial fibrillation (AF) and chronic obstructive pulmonary disease (COPD) ( Table 2 ). 1,9,23–29 Patients with HFpEF often have poor QoL, similar to patients with end‐stage renal disease, and have substantial limitations to their daily activities 22,30 . However, despite the established negative effect on QoL, variability exists in how these co‐morbidities can affect patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the burden related to HFpEF can typically be attributed to a high prevalence of co‐morbidities, such as diabetes, obesity, hypertension, anaemia, chronic kidney disease (CKD), atrial fibrillation (AF) and chronic obstructive pulmonary disease (COPD) ( Table 2 ). 1,9,23–29 Patients with HFpEF often have poor QoL, similar to patients with end‐stage renal disease, and have substantial limitations to their daily activities 22,30 . However, despite the established negative effect on QoL, variability exists in how these co‐morbidities can affect patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 9 , 23 , 24 , 25 , 26 , 27 , 28 , 29 Patients with HFpEF often have poor QoL, similar to patients with end‐stage renal disease, and have substantial limitations to their daily activities. 22 , 30 However, despite the established negative effect on QoL, variability exists in how these co‐morbidities can affect patient outcomes. For example, data from a large registry study in the Middle East showed no difference in mortality or rehospitalization rates between patients with HFpEF with or without diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…6 Apesar da praticidade, a avaliação da perfusão feita pelo médico não é suficientemente confiável 7 e depende da experiência do profissional, 8,9 posto que fornece informações subjetivas. 10 Logo, parâmetros prognósticos objetivos que podem ser facilmente obtidos em um atendimento de emergência seriam úteis no manejo da IC aguda.…”
Section: Introductionunclassified